PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABAPADA PERUSAHAAN DASAR DAN KIMIA PERIODE 2013-2016 - EKA PUTRA, FAISHAL; KUSUMANINGTIAS, ROHMAWATI (Jurnal Akuntansi AKUNESA, 2018)
This study examines the effect of The Corporate Governance to the earnings management. The earnings management is proxied by the discretionary accrual value using the modified jones formula. This research model uses a sample of manufacturing companies listed on the Indonesia Stock Exchange in Basic Industry and Chemical Industry Sector. The samples are chosen by the using purposive sampling technique during the study period, 2013-2016. Data were analyzed using linear regression. The results showed that earnings management did not affect the size of the board of commissioners, the proportion of independent commissioners, managerial ownership, institutional ownership, but had a positive effect on the audit committee. If the value of discretionary accruals in a company rose, the supervision of audit committee monitoring would also increase and strengthen supervision.Keywords: Corporate Governance, Earnings Management, Discretionary Accrual